Pelayanan Jam Kunjungan Warga Binaan Di LembagaPemasyarakatan Terbuka Kelas IIB Nusakambangan - Priliska Salsabila; Esti Ningrum; Haris Kusumawardana; Iskatrinah (Cakrawala Hukum: Majalah Ilmiah Fakultas Hukum Universitas Wijayakusuma, 2024)
This research aims to determine the visiting hours service for inmates atthe Class IIB Nusakambangan Open Penitentiary and to find out theobstacles faced in the visiting hours service for Inmates at the Class IIBNusakambangan Open Penitentiary. The approach method used in thisresearch is a normative juridical research method and the analysis in thisresearch uses a qualitative analysis method. The results of the research atthe Class IIB Nusakambangan Open Penitentiary, namely that visitinghours services for inmates at the Class IIB Nusakambangan OpenPenitentiary were carried out in accordance with the rules stipulated inthe Operational Standards, Service Standards and GovernmentRegulation No. 99 of 2012 concerning Requirements and Procedures forthe Implementation of the Rights of Inmates in Prisons with theimplementation of visiting schedules, guarantees provided and servicesfrom other visiting hours and obstacles faced in serving visiting hours forinmates at the Class IIB Nusakambangan Open Penitentiary, namelylimited crossings for to the Nusakambangan Open Prison location in thespecial Nusakambangan Island Correctional Area and strict procedures,namely administration regarding the Village Head's certificate. However,despite the obstacles, the Class IIB Nusakambangan Open Penitentiary isworking as a solution, namely providing relief for the Village Head'scertificate to be followed up on the next visit provided that the visitor stillhas one Family Card and continues to provide the best service byproviding video call services so that the WBP can still communicate withtheir families.